2018
DOI: 10.1159/000493001
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound for the Differential Diagnosis of Respiratory Distress in Neonates

Abstract: Background: Respiratory distress (RD) is the most common neonatal illness. Lung ultrasound (LUS) is a technique previously tested in neonatal studies on RD, but literature regarding its routine clinical applicability is still lacking. Objective: To assess the concordance between LUS performed by neonatologists with different training levels and chest X-ray (CXR) for the diagnosis of RD in newborns during the first 24 h of life. Methods: We enrolled newborns with RD during the first 24 h of life. Patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 23 publications
9
97
0
7
Order By: Relevance
“…It can be used to predict the need for respiratory support in the first hours of life or the need for surfactant administration in preterm infants . LU is reproducible and reduces the number of thoracic X‐rays performed in the NICU . It is increasingly recognized as a useful tool in very low birth weight infants (VLBWI) with BPD.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to predict the need for respiratory support in the first hours of life or the need for surfactant administration in preterm infants . LU is reproducible and reduces the number of thoracic X‐rays performed in the NICU . It is increasingly recognized as a useful tool in very low birth weight infants (VLBWI) with BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound is subjective in nature. Studies have demonstrated a high inter‐observer agreement among clinicians trained in lung ultrasound, independent of the clinicians' levels of experience . Further research is needed to determine whether there is agreement between different centres with varying ultrasound equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Schmölzer (2012) 7 Compares respiratory function monitoring guided resuscitation to clinical assessment 49 Respiratory function monitoring results in less mask leaks and decreased use of excessive tidal volumes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Clinicians could use the information obtained from LUS to help them decide to apply an exogenous surfactant without further deterioration of oxygenation. 6,7 Despite the widespread use of LUS in the diagnosis and management of lung diseases, no study in the literature has compared the effectiveness of different surfactants using LUS screening. In a study by Gargani et al, 25 parenchymal abnormalities that were determined by LUS preceded FiO 2 changes in an ARDSinduced animal model.…”
Section: Discussionmentioning
confidence: 99%